A general transfer function representation for a class of hyperbolic distributed parameter systems - Bartecki, Krzysztof (Zielona Góra: Uniwersytet Zielonogórski)
Results of transfer function analysis for a class of distributed parameter systems described by dissipative hyperbolic partial differential equations defined on a one-dimensional spatial domain are presented. For the case of two boundary inputs, the closed-form expressions for the individual elements of the 2×2 transfer function matrix are derived both in the exponential and in the hyperbolic form, based on the decoupled canonical representation of the system.
Keywords: distributed parameter system; hyperbolic systems; partial differential equations; transfer function; heat exchanger